Dermatology an illustrated colour text - Gawkrodger, David J.; Ardern-Jones, Michael R (Illustrated colour text, 2012)
This book gives information to medical students, those preparing for the MRCP and MRCGP examinations and specialist nurses, this book presents a accessible format, using double page spreads for each topic